COMPARATIVE EFFICACY OF INTERMITTENT AND DAILY DOXAZOSIN THERAPY FOR LUTS ASSOCIATED WITH BPH - Nurdianto, Heru; Alif, Sabilal; Tarmono, Tarmono (Indonesian Urological Association, 2011)
Objective: To investigate the efficacy of intermittent doxazosin therapy on LUTS associated BPH. Material & Method: This study was performed between January to April 2010 enrolling 20 patients with LUTS associated BPH. Study subjects were randomly allocated to 2 therapeutic groups. The first group was assigned daily doxazosin therapy (11 patients), while the second group was assigned intermittent doxazosin therapy (9 patients). Initially all subjects were given doxazosin 2 mg daily for 2 weeks. Subsequently group I received doxazosin 2 mg daily therapy, while group II received doxazosin 2 mg every other day. All medications were taken up to 12 weeks. Outcomes were evaluated prior to therapy, and after 2, 4, 8, and 12 weeks of therapy. Efficacy of doxazosin therapy was measured by International Prostate Symptom Score (IPSS), peak urinary flow rate (Q max), and residual urine volume. Statistical analysis was performed to evaluate difference in efficacy between the treatment groups. Results: Daily doxazosin therapy for 2 weeks resulted in significant improvement of Q max and IPSS. After 4, 8, and 12 weeks significant improvement was maintained in both daily and intermittent groups, as measured by Q max, residual urine volume and IPSS. There were no significant differences in Q max, residual urine volume, and IPSS between the daily and intermittent groups at 4, 8, and 12 groups. Conclusion: There were significant improvements of Q max, residual urine and IPSS at 2 to 12 weeks in daily as well as intermittent doxazosin therapy groups. There were no significant differences in efficacy between daily and intermittent therapy groups